2018
DOI: 10.21470/1678-9741-2017-0108
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effects of Atorvastatin and Ischemic Postconditioning Preventing on the Ischemia and Reperfusion Injury: Experimental Study in Rats

Abstract: IntroductionReperfusion injury leads to systemic morphological and functional pathological alterations. Some techniques are already estabilished to attenuate the damage induced by reperfusion. Ischemic preconditioning is one of the standard procedures. In the last 20 years, several experimental trials demonstrated that the ischemic postconditioning presents similar effectiveness. Recently experimental trials demonstrated that statins could be used as pharmacological preconditioning.Methods41 Wistar rats (Rattu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…In recent years, peroxisome proliferator activated receptor gamma (PPARγ), long noncoding RNAs (lncRNAs), and microRNAs (miRNAs) have been reported to play important roles to relieve hepatic I/R injury 6‐8 . In animal experiments, ischaemic pre‐conditioning and low‐temperature reperfusion alleviated hepatic I/R injury, but these preclinical findings are not yet translatable to clinical procedures 9,10 . Currently, there are few effective therapeutic strategies for protecting against I/R‐induced hepatic injury 2 …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, peroxisome proliferator activated receptor gamma (PPARγ), long noncoding RNAs (lncRNAs), and microRNAs (miRNAs) have been reported to play important roles to relieve hepatic I/R injury 6‐8 . In animal experiments, ischaemic pre‐conditioning and low‐temperature reperfusion alleviated hepatic I/R injury, but these preclinical findings are not yet translatable to clinical procedures 9,10 . Currently, there are few effective therapeutic strategies for protecting against I/R‐induced hepatic injury 2 …”
Section: Introductionmentioning
confidence: 99%
“…At present, studies on renal ischemia-reperfusion injury mainly focus on Ca 2+ overload, cell apoptosis, activation of inflammatory response mechanism, oxygen free radical increase and other areas related to oxidative stress and immune response [19][20][21] . At present, in addition to shortening the time of ischemia reperfusion and local low temperature ice compress, studies on protective measures against renal ischemia reperfusion injury also include: ischemic preconditioning, ischemic postconditioning, stem cell transplantation, and new drug therapy [22][23][24][25] . However, recent studies by Arantes et al 26 showed that both ischemic preconditioning and post-ischemic treatment, whether alone or in combination, could not contribute to the protection of renal function and could not play a protective role in tubular cell injury after acute renal ischemia-reperfusion injury.…”
Section: ■ Discussionmentioning
confidence: 99%
“…De Almeida et al illuminated that hepatic preconditioning ameliorated liver IRI by reducing lipid peroxidation [ 15 ]. In addition, hypothermic preconditioning, remote ischemic preconditioning (RIPC), and pharmacological pretreatment with statins are a benefit to IRI [ 16 , 17 , 18 ]. Although ischemic preconditioning protects organs against IRI, the ischemic preconditioning time is very critical.…”
Section: Current Strategies For Ameliorating Liver Ischemia-reperfmentioning
confidence: 99%
“…In the stage of reperfusion, ischemic postconditioning can also be used to ameliorate IRI [ 21 ]. Ischemic postconditioning alone or ischemic postconditioning combined with statin pretreatment could ameliorate reperfusion injuries [ 16 , 22 ]. However, application of ischemic postconditioning in tissue protection is also restricted due to the diversity in tissues’ physiological requirements [ 23 ].…”
Section: Current Strategies For Ameliorating Liver Ischemia-reperfmentioning
confidence: 99%